Molecular scale studies that inform trace element sulfide evaporation and atomization behavior during coal combustion. (15th January 2017) - Artemyeva, Anastasia A.; Seames, Wayne S.; Pierce, David T.; Kozliak, Evguenii I.
Highlights: GFAAS provides insights into trace element (TE) sulfides speciation during coal combustion. TGA-DSC was used under varied N2 flow rates to study microaerobic regimes of TE evolution. Antimony trisulfide demonstrated strong binding affinity to the carbon surface. Selenium disulfide tends to form molecular clusters prior to vaporization. TE sulfide evaporation is the rate limiting step. Abstract: Understanding the chemical mechanisms of trace element (TE) evolution is essential for accurate modeling of coal combustion. A novel graphite furnace atomic absorption spectrometry (GFAAS) method was used to simulate the evaporation and atomization behavior of TE sulfides (arsenic, antimony and selenium) in the two distinct microenvironments that mineral inclusions and exclusions experience during the onset of coal combustion. Additional insights were obtained using thermogravimetric analysis-differential scanning calorimetry (TGA-DSC). Potassium polysulfide was used as an additive to water to facilitate the dissolution of all three TE sulfides. TE sulfides in inclusions were studied by adding the test mixture to a graphite tube in a reducing (anaerobic) micro-environment whereas the TE evolution in excluded sulfide minerals was studied by blocking the graphite tube surface with an inert ZrO2 or WO3 coating. Arsenic sulfide, As2 S3, exhibits a lower Arrhenius activation energy of atomization, Ea, than that of the corresponding oxide in both mineral inclusions and exclusions, apparently because of the availability of a specific facile path to atomization. A higher Ea was observed for antimony sulfide, Sb2 S3, than that of the corresponding oxide from inclusions and is most likely due to its strong binding affinity to the carbon tube surface. The low GFAAS signal of selenium sulfide suggests the formation of molecular clusters, e.g., Se2, Se8 or similar mixed clusters with sulfur atoms prior to vaporization, an effect not observed for selenium oxide evaporation. For all three TE sulfides, either elemental species or unstable sulfides with low sulfur content appear to be predominant in the gas phase associated with both mineral inclusions and exclusions, with TE sulfide evaporation being the rate limiting step. Comparing the GFAAS activation energy values obtained with and without the coating showed that in a reducing micro-environment (anaerobic conditions) characteristic during the initial period of combustion for mineral inclusions, carbon merely adsorbs TE sulfides without chemical reactions. Yet TGA-DSC data showed that powdered graphite may react with TE sulfides in an oxidizing micro-environment (microaerobic conditions), such as those experienced during the later period of combustion for inclusions and during the entire combustion period for exclusions thus accelerating TE evolution without making qualitative changes in the vapor composition.